Penerapan Kurikulum Merdeka Di PAUD Sinar Mutiara Sumbawa - Pardarina, Novi; Gustia Haryati; Inneke Octafia Utami (Arus Jurnal Pendidikan, 2025)
This research describes the implementation of the Merdeka Curriculum at PAUD Sinar Mutiara, Sumbawa, West Nusa Tenggara. The focus includes teachers' learning strategies, assessment approaches, project activities, as well as challenges and support in implementation. Using case study methods and a qualitative approach, data were collected through interviews, observations, and documents. The analysis was conducted thematically with data reduction, categorization, and descriptive narration. The results show that teachers have adopted the principles of the Merdeka Curriculum, such as play-based learning and formative assessment, despite facing resource limitations. The main challenges are the lack of training and learning resources, as well as the variation in teachers' understanding. These findings are expected to assist educators and policymakers in developing implementation strategies for the Merdeka Curriculum that are more suited to regions with limited resources.